Electroactive 3D Printed Scaffolds Based on Percolated Composites of Polycaprolactone with Thermally Reduced Graphene Oxide for Antibacterial and Tissue Engineering Applications - Carolina Angulo-Pineda; Kasama Srirussamee; Patricia Palma; Victor M. Fuenzalida; Sarah H. Cartmell; Humberto Palza (My University, 2020)
Applying electrical stimulation (ES) could affect different cellular mechanisms, thereby producing a bactericidal effect and an increase in human cell viability. Despite its relevance, this bioelectric effect has been barely reported in percolated conductive biopolymers. In this context, electroactive polycaprolactone (PCL) scaffolds with conductive Thermally Reduced Graphene Oxide (TrGO) nanoparticles were obtained by a 3D printing method. Under direct current (DC) along the percolated scaffolds, a strong antibacterial effect was observed, which completely eradicated S. aureus on the surface of scaffolds. Notably, the same ES regime also produced a four-fold increase in the viability of human mesenchymal stem cells attached to the 3D conductive PCL/TrGO scaffold compared with the pure PCL scaffold. These results have widened the design of novel electroactive composite polymers that could both eliminate the bacteria adhered to the scaffold and increase human cell viability, which have great potential in tissue engineering applications.
Keywords: Polycaprolactone; Viability assay; Biocompatibility; Graphene and Nanomaterials Applications